Morphological analysis of the trachea and pattern of breathing in βENaC-Tg mice - Bonora, Massimo; Riffault, L.; Marie, S.; Mall, Marcus A.; Clement, A.; Tabary, O. (Respiratory physiology & neurobiology, 2011)
Cystic fibrosis (CF) is caused by mutations in the CFTR (cystic fibrosis transmembrane conductance regulator) gene which is a Cl− channel and a regulator of the epithelial Na+ channel (ENaC). We have recently shown that newborn CFTR-deficient mice exhibit abnormalities of the tracheal cartilage leading to altered ventilation (Bonvin et al., 2008). However, the mechanism by which a lack of CFTR causes tracheal cartilage defects remains unknown. The main goal of the present study was to determine whether the development of airway cartilage defects is related to ENac channel dysfunction. We thus performed macroscopic analysis of the trachea and explored ventilatory function in adult βENaC-overexpressing (βENaC-Tg) mice with airway Na+ hyperabsorption and “CF-lung” lung disease, at 2 and 5 month of age. Only minor cartilaginous abnormalities were observed in 8 out of 16 βENaC-Tg mice and in 2 out of 20 littermate controls. Breathing pattern was progressively altered in βENaC-Tg mice as evidenced by a significant decrease in respiratory frequency. Our results suggest that Na+ hyperabsorption alone is not a major contributor to the development of tracheal malformation observed in CF mice and that breathing pattern changes in βENaC-Tg mice likely reflect airflow limitation due to airway mucus obstruction.